2019
DOI: 10.1007/s10393-019-01416-4
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Novel Hepatozoon sp. in Giant Pandas (Ailuropoda melanoleuca)

Abstract: Hullalso provided valuable assistance with this project, for which the authors are very grateful. This project was generously funded by donations from David M. Rubenstein and family, and Judy and John W. McCarter, Jr. Generous support was also provided by the Morris Animal Foundation through our training partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Infections with species of Hepatozoon are usually subclinical in most mammalian hosts; only canid and felid species are of veterinary importance (Pawar et al 2011, Modrý et al 2017, Yu et al 2019. High prevalence and low virulence of infection with species of Hepatozoon in bears were reported in some studies (Uni et al 2003, Kubo et al 2008, Ikawa et al 2011, Pawar et al 2011.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections with species of Hepatozoon are usually subclinical in most mammalian hosts; only canid and felid species are of veterinary importance (Pawar et al 2011, Modrý et al 2017, Yu et al 2019. High prevalence and low virulence of infection with species of Hepatozoon in bears were reported in some studies (Uni et al 2003, Kubo et al 2008, Ikawa et al 2011, Pawar et al 2011.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an unidentified species of Hepatozoon in the Hokkaido brown bears (Ursus arctos yesoensis Lydekker) (Kubo et al 2010) and a novel Hepatozoon sp. in giant panda (Ailuropoda melanoleuca David) in USA (Yu et al 2019) were reported. By contrast, species of Hepatozoon were not found in American black bears (Ursus americanus Pallas) in the United States (Crum et al 1978) and in European brown bears (Ursus arctos Linnaeus) in Sweden (Mörner et al 2005).…”
mentioning
confidence: 99%
“… Intestinal tract Chengdu, Sichuan 2019 Deng et al (2019) Hepatozoon sp. Blood USA, UK, and China 2019 Yu et al (2019) Tick Ixodex granulatus Body surface Gansu Wenxian 1984 Li et al (2013) Ixodex acutitarsus Body surface Sichuan Tianquan; Sichuan Wenchuan; Gansu Wenxian 1984 Li et al (2013) Ixodex ovatux Body surface Sichuan Tianquan; Sichuan Wenchuan; Sichuan Baoxing; Gansu Wenxian 1987 Ma (1987) Haemaphysalis flava Body surface Sichuan Wenchuan; Sichuan Pingwu; Sichuan Beichun; Gansu Wenxian 1984 Li et al (2013) Haemaphysalis aponommoides Body surface Sichuan Pingwu 1985 Li et al (2013) Haemaphysalis hystricis Body surface Sichuan Tianquan 1985 Li et al (2013) Haemaphysalis longicornis Body surface Sichuan Pingwu 1985 Li et al (2013) Haemaphysalis kitaotai Body surface Sichuan Pingwu; Sichuan Beichun 1987 ...…”
Section: Parasitic Infections/infestations Reported In Giant Pandasmentioning
confidence: 99%
“… Oocyst PCR Deng et al (2019) Hepatozoon sp. Oocyst Microscopy and PCR Yu et al (2019) Tick Imago Microscopy and PCR Qiu (1987) ; Yu et al (1998) ; Cheng et al (2013) ; Chorioptes panda Imago Microscopy Ye (1986) ; Wang et al (2001) General protocols of microscopic diagnosis: The feces, vomit, intestinal contents (for necropsy), blood or tissue samples, or surface skin samples of giant pandas were obtained, and then subjected to the direct, smear, or stain observation under the microscopy. The parasites were preliminarily identifed based on the morphology, size, coloration, refraction of the eggs/oocysts/cysts/larva, or adult of the parasites, as well as the biological characteristics of the parasitic host.…”
Section: Parasitic Infections/infestations Reported In Giant Pandasmentioning
confidence: 99%
See 1 more Smart Citation